Banana Bark as A Part of Acoustic Design Unit by Hybrid Technology Application - Maharani Dian Permanasari; Dwinita Larasati; Dian Widiawati (ITB Journal Publisher, LPPM ITB, 2014)
Abstract. Banana bark is one of tropical indigenous natural resources that can be used as main material for many products. Being a fast-growing renewable material, it is durable and has natural patterns that people find visually attractive. Naturally, its textures and patterns are its main values; therefore it has the potential to be developed further. This research is needed to optimize the growth of small craft industries of banana bark, including the community where production activities take place, and also to provide information or reference of banana bark utilizations. Previous experiments conclude that banana bark has porous structure, high flexibility, relatively water-resistant due to its natural wax coating that resists water droplets, unless being washed down immensely. Also, due to its softwood- and paper-like properties, ithas many possibilities to be formed and processed into various functional products, mostly as craft products. In the subsequent study, the research about the utilization of banana bark in small industries starting from the harvesting system, handling problems in raw material supply, applying proper technology in improving the material's quality, improving the human-resource working culture by appropriate technologies, and also innovating the product's designs. The recommended designs can be implemented to improve the performance and qualities of banana bark products.Keywords: applied technology; banana bark; renewable materials; design; sustainability.